2002
DOI: 10.1001/jama.288.9.1116
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Loss and Fatigue in Residency Training

Abstract: ONG WORK HOURS ARE A TIMEhonored tradition in most residency programs. Demanding schedules are often said to be necessary for learning and development of professionalism. The use of resident physicians to provide relatively inexpensive coverage has also become an important economical factor for teaching hospitals within the United States. Recent studies of the negative effects of sleep loss and fatigue, however, call this model into question. Any consideration of the impact of sleep loss and fatigue on medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
205
0
14

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(222 citation statements)
references
References 87 publications
3
205
0
14
Order By: Relevance
“…The total number of available residents was 40 residents. However, we eliminated N residents who did not meet the following inclusion criteria: (1) engaged in inpatient treatment for at least one month and (2) performed night duty at least twice. Exclusion criteria were (1) a history of sleep disorder or serious comorbid illness (i.e., diabetes, epilepsy); (2) current use of prescription sedative or stimulant; (3) not engaged in at least three night duty shifts during a 30-day period; and (4) right-handedness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of available residents was 40 residents. However, we eliminated N residents who did not meet the following inclusion criteria: (1) engaged in inpatient treatment for at least one month and (2) performed night duty at least twice. Exclusion criteria were (1) a history of sleep disorder or serious comorbid illness (i.e., diabetes, epilepsy); (2) current use of prescription sedative or stimulant; (3) not engaged in at least three night duty shifts during a 30-day period; and (4) right-handedness.…”
Section: Methodsmentioning
confidence: 99%
“…However, most residents are subject to considerable psychological stress, fatigue, and sleep deprivation, which has a major impact on all aspects of their lives, including detrimental effects on learning and clinical performance [1]. Numerous studies have linked fatigue and sleep deprivation of resident physicians to poor performance in neurobehavioral testing, lack of motivation, and attentional failure [2,3]. Disturbed sleep not only reduces the quality of life, but also deteriorates the psychological well-being of resident physicians [4].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This heightened attention has been driven by a growing body of literature on the deleterious effects of sleep deprivation on residents' wellbeing and performance. 2,3,[7][8][9][10] Studies have identified many domains affected by fatigue, including professionalism, learning, errors, and completion of complex cognitive tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Entre os EM e MR, a privação do sono atinge status de condição cotidiana. As perturbações na dinâmica do sono podem expor estes indivíduos a diversos transtornos, entre eles: alterações cognitivas [43][44] ; dificuldade de aprendizado e de memorização e falta de motivação 45 ; e, com freqüência, causam irritabilidade, ansiedade e depressão 7,46 . Mais recentemente, estudos têm salientado a importância do sono no controle da massa corporal e na liberação de hormônios que atuam no controle da ingestão alimentar [47][48][49][50][51] , aspectos ainda não investigados entre EM ou MR.…”
Section: Hábitos E Qualidade Do Sonounclassified
“…O excesso de atividades acadêmicas na universidade e durante o aperfeiçoamento profissional na residência pode influenciar de forma negativa o estilo de vida de estudantes de Medicina (EM) e médicos residentes(MR) [2][3][4][5][6][7][8][9][10][11] . De maneira especial, destacam-se as consequências deletérias desta rotina sobre o comportamento alimentar, o nível de atividade física e o padrão de sono.…”
Section: Introductionunclassified